Causes of conflict and effective methods to conflict management at Islamic secondary schools in Yala, Thailand - Salleh, Mohamad Johdi; Adulpakdee, Apitree (International Group for Consulting and Training (IGCT), 2012)
This study presents the perceptions of teachers and school principals toward the causes of conflict and effective methods to conflict management at selected Islamic private secondary schools in Yala Province, Thailand. The sample of the study was 313 respondents which consist of 11 principals and 302 teachers. The instruments used were survey questionnaire and interview with the selected respondents. The data was processed using the Statistical Package for Social Science (SPSS) version 15.0 for Windows. The results show, the principals perceived that the main cause of conflicts occurred in school was „ambiguously defined responsibilities‟ and the teachers agreed that „different perception‟ was the major cause of conflict in school. Interestingly, both principals and teachers were strongly agreed that the most effective method to solve conflict is to „identify the causes and take appropriate steps to the solutions‟. Moreover, the findings suggest that the best solution of conflict is by applying Islamic principles such as shura,halaqoh and using the Qu‟ran and Hadith to guide them out of conflicts. It is hope that the findings of this study may guide the principals, teacher-administrators, educational leaders, teachers, and all group or individual in educational organization to manage conflicts wisely and successfully towards the harmonious working environment with optimum productivity in the era of globalization, especially the principals and teachers of Islamic and government schools in Thailand.